Mathematical Modeling of High-risk Behaviors in Reformation and Social Assistance Centers - Khademi, Nahid; Khoramdad, Malihe; Shakiba, Ebrahim; Barkhordar, Nasrin; Rostamian, Hassan; Saeidi, Shahram; Zangeneh, Alireza (International Journal of Engineering and Technology, 2018)
There is an increasing rate of high-risk behaviors in women, particularly those in prisons and high-risk places. This study was aimed to determine the high-risk behaviors among women residing in reformation and social assistance centers of Kermanshah province, Iran.In this cross sectional study, 480 women living in reformation and social assistance centers, central prisons, social welfare centers, suburban areas, high-risk neighborhoods and hangouts; were randomly selected. The primary data were collected via demographic and high-risk behavior questionnaire. To detect HIV infection, a rapid test was used as well as ELISA test in suspected cases. Statistical analysis was performed using Chi Square and Pearson Correlation Coefficient tests. The most prevalent high-risk behaviors in the subjects were addictive drug abuse (73.5%), arrest by judicial centers (59.2%), illegitimate sexual contacts (52.3%), and suicide (52.3%), respectively. The rapid HIV test revealed a positive correlation co-efficiency between HIV-positive individuals with crystal meth abuse (r=0.119, P=0.035).Associations were also observed between smoking and narcotic drug abusing (p<0.001) and with drinking alcohol (r=0.265, p<0.001). A history of suicide with a history of imprisonment also showed a positive correlation. A high prevalence of drug abusing, illegitimate sexual contacts, as well as transmission of HIV infection due to high-risk sexual contacts and injection drug addiction among the women were among the most significant findings of the survey. These observations highlight the importance of the of authorityâ€™s attention to design better policies and to implement them in order to reduce or prevent the resulting social harms.Â Â